Menstruation Matters: (De)constructing menstrual preparation as reproductive labour-work in rural Zimbabwe - Ncube, Nolwazi Nadia (Department of Sociology, 2022)
In this dissertation I focus on the practices and socio-cultural beliefs associated with menstruation that are held by rural Ndebele women and girls in Zimbabwe. I examine the embodied experience of menstruation (ukungena esikhathini – in the African language, isiNdebele) as an in-road to locating gender gaps in international development discourse. I do this in order to highlight why ‘menstruation matters'. The dissertation zooms in on Zimbabwe's policy landscape and the ways in which it treats menstruation as a problem to be solved through technical solutions like the provision of free sanitary wear without considering that indigenous peoples like the Ndebele have successfully prepared for and managed menstruation as a colonial antecedent. The study draws on the narratives of three generations of rural Ndebele women: 10 grandmothers (50-79 years), 7 mothers (30-49 years) and 11 daughters (15-29 years) in the Umzingwane District of Zimbabwe to demonstrate that even in the absence of underwear and ‘modern' commodified sanitary wear like pads, tampons and menstrual cups, rural indigent women innovate their own strategies for menstruation matters. The study identifies that the treatment of menstruation as a problem to be remedied through technical solutions is part of a legacy of the historical pathologisation of menstruation in the West. It finds that menstrual preparedness is more complex than just providing menstruating women and girls with sanitary wear but is constituted by a whole system of reproductive labour-work that transmits information that equips girls for adulthood and its corresponding responsibilities. This labour-work is carried out by a network of female relatives, school peer educators, teachers, and even male relatives – each of whom represent gatekeepers of menstrual knowledge and practices. In so doing, I challenge heteronormative gender binaries by giving a glimpse into the female fathers (obabakazi) and male mothers (omalume) who also play a role in bringing up Ndebele girls to be healthy, educated and productive adults. Once a Ndebele girl (intombazana) begins to menstruate, she now represents an adolescent girl (intombi) and proxy adult on the cusp of womanhood, and expectations around her role within the household change. She is intentionally initiated into an intensifying world of domestic chores for girls (imisebenzi yamankazana) that inscribe her gendered social identity. After ménarche, intombi is expected to be concertedly productive as well as reproductively mature – i.e., (re)productive. This induction into an increasing burden of reproductive labour-work initiates girls into the world of gender and women's work that moulds them into adult women (abafazi); future wives (omakoti), dutiful daughters-in-law (omalukazana) and mothers (omama).